Improvement of Address Resolution Security in IPv6 Local Network using Trust-ND - Supriyanto Praptodiyono; Iznan H. Hasbullah; Mohamed Anbar; Raja Kumar Murugesan; Azlan Osman (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
The current Internet infrastructure IPv4 uses Address Resolution Protocol to resolve the neighbors MAC address if not known. IPv6 is the next generation communication protocol used today to overcome the exhaustion of IPv4 addresses. IPv6 uses Neighbor Discovery Protocol (NDP) to do the address resolution and not ARP. NDP lacks security and hence the address resolution mechanism is vulnerable to various attacks that include man-in-the-middle and Denial of Service. Secure Neighbor Discovery (SeND) mechanism that was introduced to solve this problem is highly complex and the message size is large. This paper introduces Trust-ND mechanism to secure the address resolution in IPv6 local network. Experiments were done and analysis on the experimental result shows the Trust-ND could decrease the complexity of SeND. The processing time of NDP message could be reduced from 1076 times for SeND mechanism to only 1.9 times for Trust-ND. DOI: http://dx.doi.org/10.11591/telkomnika.v13i1.6929